Thinking about the unthinkable in a highly proliferated world - Murdock, Clark A.; Karako, Thomas; Williams, Ian; Dyer, Michael (CSIS report., 2016)
This study explores how a world with numerous nuclear states might function and what it would mean for our present conceptions of deterrence, for the place of the United States in the international order, and for international order itself.